2014
DOI: 10.1155/2014/369360
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Delayed Internet Worm Propagation Model with Impulsive Quarantine Strategy

Abstract: Internet worms exploiting zero-day vulnerabilities have drawn significant attention owing to their enormous threats to Internet in the real world. To begin with, a worm propagation model with time delay in vaccination is formulated. Through theoretical analysis, it is proved that the worm propagation system is stable when the time delay is less than the thresholdτ0and Hopf bifurcation appears when time delay is equal to or greater thanτ0. Then, a worm propagation model with constant quarantine strategy is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Some research achievements [10][11][12] showed that the spread dynamic system of malware would be unstable and bifurcation and chaos would appear. Considering the fact that the intrusion detection system (IDS) may lead to time delay, Yao et al [13][14][15] obtained the threshold of time delay when Hopf bifurcation occurred. Pulse quarantine strategy [16] also has been taken to constrain the propagation of worms in network.…”
Section: Introductionmentioning
confidence: 99%
“…Some research achievements [10][11][12] showed that the spread dynamic system of malware would be unstable and bifurcation and chaos would appear. Considering the fact that the intrusion detection system (IDS) may lead to time delay, Yao et al [13][14][15] obtained the threshold of time delay when Hopf bifurcation occurred. Pulse quarantine strategy [16] also has been taken to constrain the propagation of worms in network.…”
Section: Introductionmentioning
confidence: 99%
“…First, the bandwidth resources consumed in the virus control process should be measured and incorporated in the cost. Second, the optimal dynamic control problem should be investigated under sophisticated epidemic models such as the impulsive epidemic models [51,52], the stochastic epidemic models [53][54][55], and the epidemic models on time-varying networks [56][57][58]. Last, it is rewarding to apply the methodology developed in this paper to the optimal dynamic control of rumor spreading [59][60][61].…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…Considering the fact that the recovered computers may be infected again after a temporary immunity period, Zhang and Yang [19] proposed a computer virus model with two delays based on the work in [18] and studied the Hopf bifurcation by regarding the possible combinations of the two delays as a bifurcation parameter. In addition, many researchers introduced the quarantine strategy into mathematical models and investigated the Hopf bifurcation of the models in order to describe dynamics of computer viruses in a network [20][21][22][23]. Recently, Zhang and Wang [24] proposed the following SLBQRS (Susceptible-Latent-Breaking-Quarantined-Recovered-Susceptible) computer virus model with latent and breaking-out over the Internet:…”
Section: Introductionmentioning
confidence: 99%